Chimeric ALT Plus TFL Perforator Flap for Breast Reconstruction Post Radical Mastectomy with Large Skin Defect - Dushyant Jaiswal; Mayur Raman Mantri; Vinay Kant Shankhdhar; Snehjeet Hemant Wagh (Indian Journal of Plastic Surgery)
A 17-year-old girl with large malignant phyllodes tumor of left breast underwent a radical mastectomy with large skin excision resulting in defect of 20 cm × 18 cm. Postoperative radiation therapy necessitated robust cover with flap. The challenge was compounded by her body habitus. Both abdomen and back were deficient as donor sites and a single-island anterolateral thigh (ALT) flap would need skin grafts, volume deficit withstanding. We harvested chimeric ALT plus tensor fascia lata (TFL) perforator free flap sparing all muscles and nerves. Microvascular anastomoses were done to the second internal mammary artery (IMA) perforator artery and vein. The donor site was closed primarily. The TFL flap territory recruited almost three times the volume of ALT territory and allowed us to create a matching breast mound in addition to covering the defect. She tolerated 40 Gy radiation well and doesn’t desire further augmentation. Consistency of ALT and TFL perforators makes this a replicable procedure.